Effect of Different Tapered Gutta-Percha Points on Push-Out Bond Strength of Two Root Canal Sealers - Suksaphar, Warattama; Tungsawat, Pakit; Wongwatanasanti, Ninnita; Lertnantapanya, Siripat; Yodmanothum, Prattana (European Journal of General Dentistry, 2025)
The purpose of this study was to compare the push-out bond strength of root canal filling with different tapered gutta-percha points of two root canal sealers.One hundred and twenty mandibular premolar teeth were prepared with a Reciproc blue file to size R50 and divided into four groups (n = 30 per group), with group 1 receiving iRoot SP with 02-tapered gutta-percha point (iRoot02), group 2 receiving iRoot SP with match-tapered gutta-percha point (iRoot50), group 3 receiving canal sealer bioactive glass (CS-BG) with 02-tapered gutta-percha point (BG02), and group 4 receiving CS-BG with match-tapered gutta-percha point (BG50). All samples were stored at 37°C and 100% humidity for 1 week. The specimens were resected at 3.5 and 5 mm from the apex, and push-out bond strength was measured using a universal testing machine.iRoot02 had the highest push-out bond strength and differed significantly from iRootR50. BGR50 produced the lowest push-out values and showed no difference from BG02.The amount of iRoot SP in the root canal filling influences the material's resistance to pushing out. It will be more resistant if the ratio of iRoot SP to gutta-percha is high. When gutta-percha points with different tapers were used, the amount of CS-BG had no effect on the push-out force.
Keywords: bioactive glass–based sealer; calcium silicate–based sealer; endodontic sealer; push-out bond strength; root canal filling